Testing and measurement techniques and applications : proceedings of the 2015 International Conference on Testing and Measurement: Techniques and Applications (TMTA 2015), 16-17 January 2015, Phuket Island, Thailand - Chan, Kennis (CRC Press, 2015)
Covering the accepted papers of the 2015 International Conference on Testing and Measurement: Techniques and Applications(TMTA2015), January 16-17, 2015, Phuket Island, Thailand. The book is divided into 6 sessions: Microwave, Ultrasonic and Acoustic Measurement and Application; Material Performance and Measuring and Testing Technique; Laser, Optics Fiber and Sensor; Industrial Autoimmunization and Measurement; Artificial Intelligence and Application; and Image, Signal and Information Processing. The book will present its readers a relatively broad and deep understanding of recent achievements